Criteria for the specialised training of highly skilled midfielders and forwards in football - Galaktionov, M.M. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to establish criteria for the specific fitness of highly skilled midfielders and forwards in football based on factor analysis data. Methods and structure of the study. The study was conducted in 2024/2025. Thirty-two highly skilled footballers from the Russian youth team took part in the study. The players’ ages ranged from 19 to 21. The study examined the indicators of the individual fitness profile of highly skilled footballers from the Russian youth team in preparation for short-term tournaments, as well as the prospects for optimising training and competitive activities based on the identification of factors that enabled the establishment of key criteria for the fitness of highly skilled midfielders and forwards. Results and conclusions. As a result of factorising the intercorrelation matrix of the initial indicators, grouped according to playing position, a factor model was obtained, presented in Tables 1–2. Analysis of the results of factor analysis among midfielder footballers showed that the physical fitness factor predominates. This factor explains 38.4% of the total variance and has the highest loadings on the following indicators: maximum lower-body strength; lower-body strength gradient; deadlift; and sit-ups. This component can be designated as the speed-strength training factor for midfielders. In this regard, it can be assumed that the structure of the training process for highly skilled footballers should be adjusted to increase the role of speed-strength and technical training, with training regimens focused on achieving an optimal level of development of the dominant aspects of fitness for players in various positions.